2019
DOI: 10.1007/s12032-019-1278-9
|View full text |Cite
|
Sign up to set email alerts
|

Real-world study of afatinib in first-line or re-challenge settings for patients with EGFR mutant non-small cell lung cancer

Abstract: Afatinib, a second-generation epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor (TKI) for mutant nonsmall cell lung cancer (NSCLC), was approved in Japan in 2014. This study evaluated clinical outcomes of afatinib in realworld practice. Medical records of patients who received afatinib for advanced EGFR-mutant NSCLC were retrospectively reviewed. In total, 128 patients were analyzed. Seventy-six patients received afatinib as the first-line setting and 52 as the re-challenge setting (i.e., after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
1
20
1
Order By: Relevance
“…For example, in the Phase III LUX-Lung trials, diarrhea, rash/acne and stomatitis/mucositis were the most common treatment-related grade 3/4 AEs with first-line afatinib [56][57][58], and diarrhea, rash/acne and dry skin were most common in the Phase III FLAURA trial of first-line osimertinib [61]. The frequencies of these AEs have been broadly confirmed in several of the large, real-world studies described above, with no unexpected safety signals reported [21,38,[45][46][47].…”
Section: Real-world Safety and Management Of Aesmentioning
confidence: 77%
“…For example, in the Phase III LUX-Lung trials, diarrhea, rash/acne and stomatitis/mucositis were the most common treatment-related grade 3/4 AEs with first-line afatinib [56][57][58], and diarrhea, rash/acne and dry skin were most common in the Phase III FLAURA trial of first-line osimertinib [61]. The frequencies of these AEs have been broadly confirmed in several of the large, real-world studies described above, with no unexpected safety signals reported [21,38,[45][46][47].…”
Section: Real-world Safety and Management Of Aesmentioning
confidence: 77%
“…In two phase 3 clinical trials, Lux-Lung 3 and Lux-Lung 6, the median PFS among patients who harbored EGFR mutations and took 40 mg afatinib as their initial dose was 10.9 and 13.6 months, respectively. A real word practice study in Japan that enrolled 128 patients reported a median PFS of 17.8 months [20], while a phase 2 study which used a lower starting dose of 20 mg afatinib that increased in 10-mg increments up to 50 mg/day, reported a PFS of 15.2 months [19]. Another phase 2 study that enrolled 40 elderly patients had a shorter PFS of 12.9 months [22].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of OS, the phase 3 Lux-Lung 3 and Lux-Lung 6 trials reported that the median OS was 31.4 and 33.3 months, respectively. Tanaka et al presented a real-world study of rst line afatinib in Japan, with a reported median OS of 39.5 months [20]. In the Giotag trial, all patients initially received 40 mg afatinib, followed by osimertinib if T790M acquired resistance was reported; the median OS was 41.3 months and the OS was as long as 45.7 months in patients with an exon 19 deletion [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations